BATIK WITH GUTTA USING RESIST TECHNIQUES - Tity Tity (Proceeding of International Conference on Art, Language, and Culture, 2017)
In Indonesia, our ancestors since prehistoric in Banten precisely, has made batik from rice pulp starch as cover the fabric, called simbut. Simbut (Sundanese) means blanket. Before wax was used for batik, our ancestors have known simbut with batik technique since a long time a go. This simbut fabrick using the resist technique, for the color barrier is used ketan rice pulp / pulut rice which is melted and mixed with liquid brown sugar. The coloring technique still uses natural dye materials of this type of herbs.Batik that the author made using gutta as cover on the design with resist technique, using silk fabric. Gutta is used as a color barrier that can prevent the rate of liquid silk paint to the unwanted place in the design/separate colors. Batik with gutta media is just an alternative media in batik to easier in the making, and speed up the production. The process of making batik using gutta is safe for children because the gutta used does not require heating. If an error occurs in applying gutta, it is easy to fix.